PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL NUMBERED - HEAD – TOGETHER (NHT) DALAM PEMBELAJARAN SISTEM KOLOID SISWA KELAS XI SMA - Kusmoro, Aris (Universitas Lambung Mangkurat, 2011)
The research on colloidal system using Numbered Head-Together method (NHT). Subjects were a class of eleventh grade students of SMA Haruai 1. This study aims to determine increasing in student learning outcomes and to evaluate the response of students towards learning using numbered head together (NHT). Classroom action research carried out in two cycles. The first cycle consisted of two action and second cycle consisted of an action. the number of students in this study amounted 24 people. data collected by tests, questionnaires, observations, and analyzed by quantitative descriptive.Â The results showed that (1) student learning outcomes using Numbered-Head-Together (NHT) has increased, (2) students responded positively to the use of method numbered head together (NHT) in colloidal systems of learning. Â Key words : Numbered head together (NHT), colloidal system, cycle, quantitative descriptive.